2013
DOI: 10.3109/13813455.2013.876049
|View full text |Cite
|
Sign up to set email alerts
|

Each of the four intracellular cysteines of CD36 is essential for insulin- or AMP-activated protein kinase-induced CD36 translocation

Abstract: Stimulation of cellular fatty acid uptake by induction of insulin signalling or AMP-kinase (AMPK) activation is due to translocation of the fatty acid-transporter CD36 from intracellular stores to the plasma membrane (PM). For investigating the role of the four Cys-residues within CD36's cytoplasmic tails in CD36 translocation, we constructed CHO-cells expressing CD36 mutants in which all four, two, or one of the intracellular Cys were replaced by Ser. Intracellular and PM localization of all mutants was simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…The evident plasma membrane localization of CD36 found in patients with NASH prompted the investigation of the possible mechanism(s) regulating the distribution of this protein. Previous studies demonstrated that insulin increases CD36 palmitoylation and rapidly stimulates the surface expression of CD36 in muscle cells[34,35]. In addition, Thorne et al consistently found that palmitoylation is necessary for the efficient incorporation of CD36 into plasma membrane rafts in melanoma cells[23].…”
mentioning
confidence: 97%
“…The evident plasma membrane localization of CD36 found in patients with NASH prompted the investigation of the possible mechanism(s) regulating the distribution of this protein. Previous studies demonstrated that insulin increases CD36 palmitoylation and rapidly stimulates the surface expression of CD36 in muscle cells[34,35]. In addition, Thorne et al consistently found that palmitoylation is necessary for the efficient incorporation of CD36 into plasma membrane rafts in melanoma cells[23].…”
mentioning
confidence: 97%
“…It has been demonstrated that plasma membrane localization and the LCFA transport function of CD36 rely on cysteine S-acylation with LCFAs, such as palmitate ( 37 ). In adipocytes, palmitoyl acyltransferases DHHC4 and DHHC5 have been shown to acylate CD36 ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Acyl protein thioesterase 1 (APT1), one of the depalmitoylating enzymes, can depalmitoylate CD36 by recruiting tyrosine kinase SYK to induce the uptake of FAs and assist in weight gain in high-fat-diet (HFD)-fed mice [49]. Furthermore, despite insulin stress and AMPK activation, mutation in one of these four sites can impede CD36 translocation from the endosomes to the plasma membrane, indicating that palmitoylation is indispensable for the cycling of CD36 [50]. However, palmitoylation of CD36 in cardiac diseases has not been studied.…”
Section: Post-translational Regulation Of Cd36mentioning
confidence: 99%